Long-Term Functional Outcomes After Sepsis for Adult and Pediatric Critical Care Patients—Protocol for a Systematic Review - Simpson, Adam; Long, Deborah; Fleischmann-Struzek, Carolin; Minogue, Jessicah; Venkatesh, Balasubramanian; Hammond, Naomi E.; Tian, David H.; Schlapbach, Luregn J. (Frontiers in Pediatrics, 2021)
Objective: Sepsis is responsible for a massive burden of disease, with a global estimate of 48.9 million cases resulting in approximately 11 million deaths annually. Survivors of sepsis may also experience long-term impairments that can persist for years after hospital discharge. These cognitive, physical and/or psychosocial deficits may contribute to a lower health related quality of life and represent a significant ongoing burden to the individual, the community and the health care system. We aim to systematically review the available evidence on long-term functional and quality of life outcomes after sepsis in children and adults. Data Sources: Medline, EMBASE, and CINAHL will be searched for eligible studies. Study Selection: Studies of adult and paediatric survivors of sepsis who had required admission to intensive care will be included. A minimum 6 month prospective follow up will be required. Accepted outcomes will be any validated measure of health-related quality of life (HRQoL) or functional deficits, using the Post-Intensive Care Syndrome (PICS) framework of cognitive, physical or psychosocial outcomes. Data Extraction: Data extraction will include information related to study characteristics, population characteristics, clinical criteria and outcomes. Data Synthesis: Studies meeting the inclusion criteria will be presented descriptively separated for pediatric and adult age groups. Meta-analysis will be attempted if sufficient primary data from several studies applying the same tests and outcomes are available. The primary outcome is HRQoL after sepsis; secondary outcomes include the functional status at follow-up. Conclusions: This systematic review will define the long-term impact of sepsis survivorship. The data will contribute to informing patient, clinician and stakeholder decisions and guide further research and resource management.